Tumor endothelial cell autophagy is a key vascular‐immune checkpoint in melanoma - Jelle Verhoeven; Kathryn A Jacobs; Francesca Rizzollo; Francesca Lodi; Yichao Hua; Joanna Poźniak; Adhithya Narayanan Srinivasan; Diede Houbaert; Gautam Shankar; Sanket More; Marco B Schaaf; Nikolina Dubroja Lakic; et al. (EMBO Molecular Medicine, 2023)
Abstract Tumor endothelial cells (TECs) actively repress inflammatory responses and maintain an immune‐excluded tumor phenotype. However, the molecular mechanisms that sustain TEC‐mediated immunosuppression remain largely elusive. Here, we show that autophagy ablation in TECs boosts antitumor immunity by supporting infiltration and effector function of T‐cells, thereby restricting melanoma growth. In melanoma‐bearing mice, loss of TEC autophagy leads to the transcriptional expression of an immunostimulatory/inflammatory TEC phenotype driven by heightened NF‐kB and STING signaling. In line, single‐cell transcriptomic datasets from melanoma patients disclose an enriched InflammatoryHigh/AutophagyLow TEC phenotype in correlation with clinical responses to immunotherapy, and responders exhibit an increased presence of inflamed vessels interfacing with infiltrating CD8+ T‐cells. Mechanistically, STING‐dependent immunity in TECs is not critical for the immunomodulatory effects of autophagy ablation, since NF‐kB‐driven inflammation remains functional in STING/ATG5 double knockout TECs. Hence, our study identifies autophagy as a principal tumor vascular anti‐inflammatory mechanism dampening melanoma antitumor immunity.